2021
DOI: 10.7554/elife.62653
|View full text |Cite
|
Sign up to set email alerts
|

A genetic screen identifies new steps in oocyte maturation that enhance proteostasis in the immortal germ lineage

Abstract: Somatic cells age and die, but the germ-cell lineage is immortal. In Caenorhabditis elegans, germline immortality involves proteostasis renewal at the beginning of each new generation, when oocyte maturation signals from sperm trigger the clearance of carbonylated proteins and protein aggregates. Here, we explore the cell biology of this proteostasis renewal in the context of a whole-genome RNAi screen. Oocyte maturation signals are known to trigger protein-aggregate removal via lysosome acidification. Our fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Microautophagy has yet to be characterized in C . elegans [ 69 ], yet, 2 recent studies provide evidence for macroautophagy-independent degradation of cytosolic cargo by the lysosome evocative of microautophagy [ 70 72 ]. Further work is needed to establish how SAPA would rely on microautophagy to stop the aggregation of certain globular proteins during core PQC failure.…”
Section: Discussionmentioning
confidence: 99%
“…Microautophagy has yet to be characterized in C . elegans [ 69 ], yet, 2 recent studies provide evidence for macroautophagy-independent degradation of cytosolic cargo by the lysosome evocative of microautophagy [ 70 72 ]. Further work is needed to establish how SAPA would rely on microautophagy to stop the aggregation of certain globular proteins during core PQC failure.…”
Section: Discussionmentioning
confidence: 99%
“…The findings regarding the Lysotracker also revealed that both PIP2 and PMA significantly affected lysosome acidification in cumulus cells, but DOG did not have this effect on these cells. In one of the recent studies, Samaddar et al (2021) revealed that suppression of lysosomal V‐ATPase, vesicle‐transport or proteasome function increases the speed of age‐dependent protein aggregation in the soma and preserves proteostasis in the ageing soma which links the processes that improve proteostasis in the immortal germ lineage. Our study, proving the assistance of PIP2 and PMA in protein degradation, raised the question of whether these factors could also cause a degradation of vital proteins which take important roles for both oocytes and cumulus cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that in vesicles with presenilin-1 (PS1) deficiency, lysosomal pH deficiency leads to a significant increase in lysosomal pH, leading to dysregulation of proteolytic enzymes (J. H. Lee et al, 2010Lee et al, , 2015. In addition, deacidification and elevated intracellular pH inhibit enzyme activity in the intimal binding compartment, thus disrupting the clearance of protein aggregates (Samaddar et al, 2021;Santerre et al, 2021). In addition, elevated endonuclease and lysosome pH may have an overall effect on the proteome.…”
Section: V-atpase and Lysosome Acidificationmentioning
confidence: 99%